Maxillary sinus raising and implant installation at the same surgical time (Research, Society and Development, 2022)
Objective: To develop a narrative review of the literature on the techniques of maxillary sinus lift and implant placement at the same surgical time as a functional treatment option for oral rehabilitation. Methodology: Review of articles on the proposed theme, all articles used are from reliable databases, being PubMed, Scielo and Google Scholar, with the ultimate objective of achieving the expected results. Discussion and results: With natural aging, the loss of dental elements is common, so dentists seek alternatives to rehabilitate patients. Most cases are treated with dental implants, however, the availability of bone in the maxilla is an important factor, since an adequate quantity and quality of bone allows its installation and contributes to the success of the treatment. Surgical techniques were developed to solve the bone deficiency in the posterior region of the maxilla and provide treatment with implants, for example, maxillary sinus lift surgery, which can be performed simultaneously with the installation of the dental implant. Final considerations: Treatment with osseointegrated implants simultaneously with maxillary sinus lift surgery is a great advantage in the area of ​​oral rehabilitation, as it reduces the number of visits and provides quality of life for patients. The results are, in most cases, satisfactory.